"Constructing human rights in the age of globalization/by Monshipouri, Mahmood ed.. [et al]" (New Delhi, 2004)
This book provides a panoramic view of a phenomenal issue that has, overnight, pervaded the whole world:Globalization and its impact on human rights. The topics it addresses are as much relevant to the politician as to the philosopher, as much relevant to the most successful corporate organization as to the common man. What adds to the contemporary pertinence of the book are the frequent references to various present day scena-rios selected from all over the world, interspersed throughout the course of the narrative. The enriching, enlightening and absorbing description is, however, surprisingly simple, fast-moving and devoid of the usual verbosity that burdens books on humanities. The comprehensive coverage and the variety of information presented on real world situations make the book valuable not only to post-graduate students of history and political science but also to those preparing for competitive examinations.
Keywords: Human rights